2005
DOI: 10.1681/asn.2004040275
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, Phosphorus, Parathyroid Hormone, and Cardiovascular Disease in Hemodialysis Patients: The USRDS Waves 1, 3, and 4 Study

Abstract: Animal studies suggest that calcium-phosphorus homeostatic abnormalities cause cardiovascular disease in uremia; few observational studies in humans have explored this. Associations in the retrospective United States Renal Data System Waves 1, 3, and 4 Study of 14,829 patients who were on hemodialysis on December 31, 1993, were examined. Mean age and duration of renal replacement therapy were 60.0 and 3.2 yr, respectively; 40.7% had diabetes. Quintiles (Q 1 to Q 5 ) of (albumin-adjusted) calcium were <8.7, 8.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
317
5
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 389 publications
(344 citation statements)
references
References 23 publications
15
317
5
7
Order By: Relevance
“…The more severe hyperparathyroidism among Blacks and South Asians may therefore be a physiologic adaptive response to maintain bone turnover. Previous studies have reported associations between high PTH and all-cause mortality (51)(52) and cardiovascular-and fracture-related hospitalizations (52), but this was observed only at PTH levels of Ͼ480 pg/ml (52), and Ͼ600 pg/ml (51), much higher than the KDOQI recommended target of 150 to 300 pg/ml. It is also not clear if the PTH levels at which the mortality, hospitalization, and fracture-risk increases vary between ethnic groups.…”
Section: Discussionmentioning
confidence: 89%
“…The more severe hyperparathyroidism among Blacks and South Asians may therefore be a physiologic adaptive response to maintain bone turnover. Previous studies have reported associations between high PTH and all-cause mortality (51)(52) and cardiovascular-and fracture-related hospitalizations (52), but this was observed only at PTH levels of Ͼ480 pg/ml (52), and Ͼ600 pg/ml (51), much higher than the KDOQI recommended target of 150 to 300 pg/ml. It is also not clear if the PTH levels at which the mortality, hospitalization, and fracture-risk increases vary between ethnic groups.…”
Section: Discussionmentioning
confidence: 89%
“…Hyperphosphatemia is a well known risk factor for all-cause and cardiovascular mortality in HD patients (27)(28)(29). It has been associated with secondary hyperparathyroidism, renal osteodystrophy, and with the development of vascular calcifications (30).…”
Section: Discussionmentioning
confidence: 99%
“…104 Phosphate toxicity RB Brown et al have shown that hypercalcemia may have predictive value in determining the negative outcome of CKD patients. 85 Although phosphate toxicity is known to promote disease progression in patients with CKD, its association with tumorigenesis is not studied in similar depth and detail. We next present evidence of this association and suggest some innovative theories of tumorigenesis.…”
Section: Phosphate Toxicity Associated With Ckdmentioning
confidence: 99%